The Trapezuntine poems in Panagiou Taphou 370 - Lauxtermann, MD (Edinburgh University Press, 2024)
In this paper I propose a new date for the Trapezuntine poems in ms. Panagiou Taphou 370 (commonly attributed to Stephen Sgouropoulos) and identify references to historical events that took place in Trebizond during the first thirty years of the fifteenth century.